Granulomatous Inflammation of the Upper Eyelid After Autologous Fat Injection. Issue 3 (May 2019) - Huh, Jungah; Yang, Sungwon; Park, Jinhwan; Lee, Hwa; Baek, Sehyun
Abstract : Abstract: A 45-year-old female came to the clinic complaining of periorbital swelling and ptosis on the left upper eyelid that had started 6 months previously. She had received an autologous fat injection in the forehead 6 months prior, and there was no other ophthalmologic history. There were no abnormal findings, including pupil, extraocular movement, or fundus examination. There was eyebrow elevation of the left upper eyelid, and the marginal reflex distance 1 was 1 mm on the left eye compared to 4 mm on the right eye. There were a 2-cm-sized round and firm mass on the left upper eyelid that was not accompanied by tenderness. Orbital computed tomography showed heterogeneous infiltration with an ill-defined margin. Excisional biopsy and levator advancement were performed on the left upper eyelid, and histological findings showed chronic granulomatous inflammation with foreign body reaction and fat necrosis. A complete history for patient presentation with autologous fat injection is important when a periorbital mass is encountered clinically because granulomatous inflammation of the eyelid may occur after autologous fat injection in the forehead and can be related to migration of the injected fat.